THE EFFECT OF PICTURE CARD MEDIA ON VISUAL-SPATIAL ABILITY AND MATHEMATICS LOGIC ABILITY IN EARLY CHILDREN (Experimental Study at Raudhatul Athfal Al Muhajirin Medan Deli) - Syaukani, Syaukani; Ananda, Rusydi; Suwardi, Suwardi (Universitas Dharmawangsa Medan, 2021)
The purpose of this study was to determine (1) the effect of picture card media on the visual-spatial ability of early childhood, (2) The effect of picture card media on the mathematical logic ability of early childhood, and (3) Differences in the effect of picture card media on visual spatial and mathematical logic abilities of early childhood. This research method is an experimental method, and this type of research is classroom action research which aims to see how far the influence of picture card media on visual spatial abilities and mathematical logic abilities of early childhood. All stages carried out in this classroom action research are actions that form a cycle which includes planning, implementation, observation and reflection. The subjects of this study were all students in groups B1 and B2 aged 5-6 years Raudhatul Athfal Al-Muhajirin Medan Deli. The results of this study are (1) Picture card media has a significant effect on children's visual-spatial abilities. This can be seen from the increase in children's visual-spatial abilities by 79% which developed very well after using picture cards. (2) Picture card media has a significant effect on children's mathematical logic skills. This can be seen from the increase in children's mathematical logic skills by 88% which developed very well after using picture cards. (3) Based on the F test that has been carried out, the picture card media has an effect on the visual spatial ability and mathematical logic ability of children together by 77.4% and the remaining 22.6% (100-77, 4) influenced by other variables. Picture Card Media, Visual Spatial Ability, Mathematical Logic Ability.